A produção desjudicializada da prova oral através de negócio processual: análise jurídica e econômica - Müller, Julio Guilherme (2016)
This thesis deals with legal and economic analysis of the procedural contracts to obtain outsourced oral evidences (outside the court) and without the direct participation of the judge, which allows the parties to use written or recorded statements of a witness. Through a deductive method, the research confirms that the hypothesis follows the cooperative procedural model and the combination of two general rules found in the procedural statutes: one that allows the parties to celebrate procedural contracts on their procedural positions;; and the one that authorizes them to produce atypical evidence. The extrajudicial production of the oral evidences directly by the parties and without the participation of the judge, made possible when transaction costs allow and the balance between the benefits and disadvantages is better than when compared to the judicial model, is an efficient option to reduce the duration of proceedings, to stimulate settlement of disputes by agreement, to prevent litigation and to improve the quality of evidence